Modern family? Paternity leave and marital stability - Daniel Avdic; Arizo Karimi (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2016)
We study the effects of unanticipated changes to the intra-household division of parental leave on family stability exploiting two parental leave reforms in Sweden. Using a fuzzy regression discontinuity design, we find that a decrease in the mother's share of parental leave increases the probability of separation among couples that were married or cohabiting at the time of the reforms. Our results also suggest a lower likelihood of cohabiting couples to upgrade to marriage. Examination of reform compliers reveal that the increased separation risk is mainly driven by more traditional couples, and among couples with previous children.
Keywords: C26; D13; J13; J31; 330; marital stability; parental leave; intra-household division; regression discontinuity